Hans Bachmann. The external relations of the less developed countries. Nueva York : Praeger Special Studies in International Economics and Development, 1968. 341 p. - Buira, Ariel (Estudios Demográficos y Urbanos, 1968)
HANS BACHMANN, The Externa! Relatians of the Less Developed Countries. Praeger Special Studies in International Economics and Development. Nueva York, 1968.